Inferring primase-DNA specific recognition using a data driven approach. Issue 20 (29th October 2021) - Soffer, Adam; Eisdorfer, Sarah A; Ifrach, Morya; Ilic, Stefan; Afek, Ariel; Schussheim, Hallel; Vilenchik, Dan; Akabayov, Barak
Abstract: DNA–protein interactions play essential roles in all living cells. Understanding of how features embedded in the DNA sequence affect specific interactions with proteins is both challenging and important, since it may contribute to finding the means to regulate metabolic pathways involving DNA–protein interactions. Using a massive experimental benchmark dataset of binding scores for DNA sequences and a machine learning workflow, we describe the binding to DNA of T7 primase, as a model system for specific DNA–protein interactions. Effective binding of T7 primase to its specific DNA recognition sequences triggers the formation of RNA primers that serve as Okazaki fragment start sites during DNA replication.